2021
DOI: 10.1016/j.pdpdt.2021.102449
|View full text |Cite
|
Sign up to set email alerts
|

The impact of delayed anti-vascular endothelial growth factor treatment for retinal diseases during the COVID-19 lockdown

Abstract: Purpose : To assess the clinical status of treatment-naive patients who had to delay 3-dose loading anti-VEGF (anti-vascular endothelial growth factor) injections during the COVID-19 lockdown, and to evaluate the effect of the delayed visual acuity treatment on spectral domain optical coherence tomography (SD-OCT) parameters. Method : A total of 55 eyes of 46 patients who were received in the study period participated in this retrospective stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 14 publications
0
9
0
Order By: Relevance
“… 2 , 27 , 28 , 36 In the end, 14 studies (including 1,931 patients) were included in the quantitative synthesis. 4 , 5 , 8 , 24 , 29 , 30 , 31 , 33 , 34 , 35 , 37 , 44 , 45 , 46 The PRISMA diagram detailing the study screening process is shown in Supplementary File, Figure S1 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“… 2 , 27 , 28 , 36 In the end, 14 studies (including 1,931 patients) were included in the quantitative synthesis. 4 , 5 , 8 , 24 , 29 , 30 , 31 , 33 , 34 , 35 , 37 , 44 , 45 , 46 The PRISMA diagram detailing the study screening process is shown in Supplementary File, Figure S1 .…”
Section: Resultsmentioning
confidence: 99%
“…All included studies were observational in nature. All studies measured changes in patients with nAMD while 10 studies measured changes in patient with DME 5 , 8 , 24 , 27 , 28 , 29 , 33 , 34 , 36 , 44 and 9 studies measured changes in those with RVO. 5 , 8 , 24 , 28 , 29 , 33 , 34 , 36 , 44 The mean length of time between the last pre-pandemic visit and the first visit during the pandemic was four months or greater for eight studies.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…DM-related diseases and RVO both lead to macular edema and loss of retinal photoreceptors and retinal pigment epithelium; these may also cause visual impairment or distortion [ 46 , 47 ]. Bulut et al also investigated the impact of delayed anti-VEGF treatment for retinal diseases and found that a six-month delay in intravitreal injection of loading doses of anti-VEGF had adverse effects in macular edema from RVO [ 48 ]. A prompt detection and treatment of these ophthalmic diseases and related chief complaints may maximize the effects of adequate eye care when it comes to cost-benefit analysis during the COVID-19 pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, for their part, patients tried to avoid exposure to the virus by delaying and avoiding elective visits [ 12 ]. During that period, patients received a reduced number of injections and less frequent medical follow-ups, which was associated with adverse outcomes in patients with RVO [ 13 ].…”
Section: Introductionmentioning
confidence: 99%